Barriers to Healthcare for People With a Learning Disability From Ethnic Minorities: Perspectives of Self‐Advocates and Carers. - Cooper‐Moss, Nicola; Umpleby, Katie; Roberts, Christina; Garner, Christie; Edwards, Aisha Hazel; Ditzel, Nicola; Butt, Jabeer; Clark, Samantha; Hatton, Christopher; Chauhan, Umesh (British Journal of Learning Disabilities, 2025)
Background: People with a learning disability from ethnic minorities experience barriers in their access to healthcare services and poorer health outcomes. This study aimed to explore the factors that contribute to these barriers and to better understand how they can be reduced. Methods: Twenty 'experts by experience' took part in experience‐based co‐design workshops to ascertain how lived experiences related to findings from a co‐designed scoping review. Audio recordings were transcribed and analysed using framework analysis. Findings: Self‐advocates and carers experienced discrimination within a range of healthcare settings; however, recognising and understanding the source was difficult. Many people reported a lack of reasonable adjustments or support services that considered their ethnic identities. Participants also experienced isolation and stigma within their own family and community networks. Access to healthcare was adversely affected by COVID‐19. Many people were unaware of the Learning Disability Register and there was insufficient support when transitioning between healthcare services. Conclusions: Services can be improved by effective communication, continuity of care and an enhanced understanding of the experiences of learning disability across different ethnic groups. Understanding an individual's needs and preferences from the first point of contact is important for the allocation of resources. Summary: People with a learning disability from ethnic minorities have problems using healthcare services.We call these problems barriers because they stop people from getting help. This means their health gets worse.We had three meetings with people from ethnic minorities with a learning disability and carers. We asked them to tell us what barriers they have when using healthcare services.People were treated unfairly in healthcare. It was difficult to know if this was because of their disability or ethnicity. They were also treated differently by their families and communities.Healthcare workers should learn how people from different ethnic groups experience learning disabilities to give better care.